New arsenate minerals from the Arsenatnaya fumarole, Tolbachik volcano, Kamchatka, Russia. XIX. Axelite, Na14Cu7(AsO4)8F2Cl2. (21st February 2023) - Pekov, Igor V.; Zubkova, Natalia V.; Agakhanov, Atali A.; Yapaskurt, Vasiliy O.; Belakovskiy, Dmitry I.; Britvin, Sergey N.; Sidorov, Evgeny G.; Kutyrev, Anton V.; Pushcharovsky, Dmitry Yu.
Abstract: The new mineral axelite, ideally Na14 Cu7 (AsO4 )8 F2 Cl2, was found in the Arsenatnaya fumarole at the Second scoria cone of the Northern Breakthrough of the Great Tolbachik Fissure Eruption, Tolbachik volcano, Kamchatka, Russia. It is associated with sylvite, halite, arsmirandite, bradaczekite, johillerite, tilasite, ericlaxmanite, lammerite, hematite, tenorite, cassiterite, pseudobrookite, aphthitalite-group sulfates, anhydrite, fluoborite, sanidine and fluorophlogopite. Axelite occurs as tabular, quadratic, rectangular or stronger distorted crystals up to 0.02 × 0.1 × 0.1 mm, sometimes combined in interrupted crusts up to 0.4 mm across overgrowing sylvite. It is transparent, sky-blue, with vitreous lustre. Cleavage was not observed. D calc is 3.662 g cm –3 . Axelite is optically uniaxial (–), ɛ = 1.650(4) and ω = 1.678(4). Chemical composition (wt.%, electron microprobe data) is: Na2 O 22.54, K2 O 0.08, CaO 0.04, MgO 0.05, CuO 26.69, P2 O5 1.75, V2 O5 0.15, As2 O5 44.14, SO3 0.04, F 1.57, Cl 3.60, –O=(F, Cl) –1.47, total 99.18. The empirical formula based on O+F+Cl=36 apfu is Na14.37 K0.03 Ca0.01 Mg0.02 Cu6.63 P0.49 V0.03 As7.59 S0.01 O32.36 F1.63 Cl2.01 . Axelite is tetragonal, P 4 bm, a = 14.5957(2), c = 8.34370(18) Å, V = 1777.51(6) Å 3 and Z = 2. The strongest reflections of the powder X-ray diffraction (XRD) pattern [ d, Å( I )( hkl )] are: 8.32(44)(001), 5.156(47)(220), 4.168(21)(002), 3.246(34)(222), 3.180(61)(331), 2.747(100)(402), 2.709(36)(511) and 2.580(29)(440). The crystal structure, solved from single-crystal XRD data ( R = 4.50%), is unique. It is based on the heteropolyhedral chains built by clusters formed by CuO4 Cl square pyramids connected with AsO4 tetrahedra. Adjacent chains are connected via common vertices of AsO4 tetrahedra with CuO4 Cl pyramids to form a heteropolyhedral pseudo-framework. Axelite is remotely related, in both structural and chemical aspects, to lavendulan-like minerals and synthetic compounds. The mineral is named in honour of the outstanding Finnish–Russian crystallographer, mineralogist and material scientist Axel Gadolin (1828–1892).